Implementation of the Kurikulum Merdeka Through the P5 Program in Islamic Religious Education Learning at SMP Tahfidz Assyifa Al Islami Parung - Ahmad Purkoni; Agus Nur Qowim (Edu Spectrum: Journal of Multidimensional Education, 2024)
This study aims to describe and analyze the implementation, challenges, and solutions in applying the Kurikulum Merdeka through the P5 program in Islamic Religious Education (PAI) learning. The research was conducted at SMP Tahfidz Assyifa Al Islami Parung using a qualitative approach and field research methodology. Data collection techniques included interviews, documentation, and observation, with data validity tested through triangulation of methods and sources. Data analysis involved data collection, reduction, presentation, and conclusion drawing. The findings reveal that the implementation of the Kurikulum Merdeka through the P5 program in PAI learning began in the fourth week of July in the 2024 academic year, focusing on entrepreneurship for seventh-grade students and democracy for eighth-grade students. However, challenges were identified, including limited teacher understanding and training regarding the P5 program, insufficient supervision from project coordinators, and inadequate module support, as the materials were primarily downloaded from the internet.